Zorotypus hukawngi sp. nov., a Fossil Winged Zoraptera (Insect) in Burmese Amber - Chen, Xin-Yu; Su, Gui-Fen (Zootaxa, 2019)
A new species of the insect order Zoraptera, Zorotypus hukawngi sp. n., is described and figured based on one not well-preserved specimen in mid-Cretaceous amber from the Hukawng Valley in northern Myanmar. Compared to known extinct zorapterans, the new species is readily distinguished by characters of the mesonotum, wings, and the spination of the metafemur and metatibia.